Trade, wages, and profits - Hartmut Egger; Peter Egger; Udo Kreickemeier (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
This paper formulates a structural empirical model of heterogeneous firms whose workers exhibit fair-wage preferences. In the underlying theoretical framework, such preferences lead to a link between a firm's operating profits on the one hand and wages of workers employed by this firm on the other hand. The latter establishes an exporter wage premium, since exporters have higher profits, given their productivity, than non-exporting firms. We estimate the parameters of the model in a data-set of five European economies and find that, when evaluated at these parameter values, the model has a high level of explanatory power. The estimates also enable us to quantify the exporter wage premium and the consequences of trade for the main variables of interest. According to our results, openness to international trade contributes to greater inequality across firms in terms of both operating profits and average wages. We also find evidence for gains from trade for all five countries, which go along with negative, but quantitatively moderate, aggregate employment effects.
urn:nbn:de:bsz:21-opus-59468
Keywords: C31; F12; F16; J31; 330; structural models; heterogeneous firms; fair wages; labour market imperfections; exporter wage premium